2012
DOI: 10.1007/s00381-012-1870-1
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of brain swelling associated with subdural hemorrhage: the role of the trigeminovascular system

Abstract: The trigeminal system may provide the anatomo-physiological link between small-volume, thin subdural bleeds and swelling of the underlying brain. This physiology may help to explain the poorly understood phenomena of "second-impact syndrome," the infant response to subdural bleeding (the "big black brain"), as well as post-traumatic subdural effusions. Considerable age-specific differences in the density of dural innervation exist; age-specific responses of this innervation may explain differences in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…86 The substrate for male vulnerability to SIDS has been suggested to be specifically reduced 5-HT binding in the brainstem. 66 Our unpublished results also showed variation in neuropeptide expression with sex: substance P was lower in female than male children and higher in female than male adults. Several conditions which involve the trigeminovascular system show a degree of sex specificity.…”
Section: Sexmentioning
confidence: 68%
See 1 more Smart Citation
“…86 The substrate for male vulnerability to SIDS has been suggested to be specifically reduced 5-HT binding in the brainstem. 66 Our unpublished results also showed variation in neuropeptide expression with sex: substance P was lower in female than male children and higher in female than male adults. Several conditions which involve the trigeminovascular system show a degree of sex specificity.…”
Section: Sexmentioning
confidence: 68%
“…In both cases inflammatory sensitization of dural trigeminal afferents was considered to be an important predisposing factor. 63 Bleeding in the human dura, which produces an inflammatory response and increased mast cell numbers, 64,65 may potentially sensitize the trigeminal system, 66 and has been implicated in inducing the trigeminocardiac reflex. 58 Krous et al 59 describe five infants with 'awake SIDS', in four of whom nasal or laryngeal stimulation was implicated in triggering a response; one infant collapsed shortly after having saline sprayed into the nostrils followed by syringe bulb suction, and three collapsed during feeds.…”
Section: The Hippocampus Seizures and Apnoeamentioning
confidence: 99%
“…This is important because such the meningeal vessels of this calibre are innervated by CGRP expressing nerves [20]. Previously, by measuring venous distensibility in humans it has been observed that GTN dilates veins more so than arteries [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains unclear whether smaller vessels are dilated in response to GTN similarly to the large ones. Elucidating this issue is important, because small size meningeal vessels are innervated by caltitonin gene-related peptide containing nerves (CGRP) [20], which suggests that small vessel dynamics may play a role in migraine pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although not evaluated in this model, the unilateral pattern of HH is unlikely to result from neck injury and/or nerve reflexes from the dura, which cause global apnea, a mechanism purported by Geddes and colleagues and others. 10,11,[41][42][43] An alternate possible mechanism is a regional metabolic mismatch between supply and demand. The exact pathophysiological mechanisms by which widespread unilateral hemispheric hypoxic-ischemic injury is initiated and propagated in children are not fully understood, but similar findings were produced in this model in the absence of angular acceleration/deceleration.…”
Section: Discussionmentioning
confidence: 99%